Donor brain death aggravates chronic rejection after lung transplantation in rats. - Zweers, N; Petersen, A; van der Hoeven, J; de Haan, A; Ploeg, R; de Leij, L; Prop, J (2004)
BACKGROUND: Many recipients of lung transplants from brain-dead donors develop bronchiolitis obliterans, a manifestation of chronic rejection. It has been shown that brain death increases inflammatory mediators and accelerates acute rejection in kidney, liver, and heart transplants. In this study, the authors investigated the hypothesis that brain death increases inflammatory mediators in the donor lung and subsequently aggravates chronic rejection of the lungs after transplantation in rats. METHODS: Brain death was induced in F344 rats by inflation of a subdurally placed balloon catheter. After 6 hr, donor lungs were assessed for influx of leukocytes, expression of cell adhesion molecules, and cytokine mRNA expression. For assessment of the lung after transplantation, lungs from brain-dead F344 rats were transplanted into WKY rats. Lung function after transplantation was monitored by chest radiographs during an observation period of 100 days. At the end of this period, the lungs were histologically examined; also, cytokine mRNA expression was measured. Lungs from ventilated living donors and living donors served as controls. RESULTS: After 6 hr of brain death, influx of polymorphonuclear cells and macrophages and expression of vascular cell adhesion molecule-1 in the donor lungs was increased. After transplantation at postoperative day 100, the lung function was significantly decreased compared with allografts from living donors. In the lung allografts from brain-dead donors, histologic symptoms of chronic rejection were obvious, including severe intimal hyperplasia but without bronchiolitis obliterans. Interleukin-2 mRNA was significantly increased in allografts from brain-dead donors compared with living donors. CONCLUSIONS: This study shows that brain death induces an inflammatory response in the donor lung and subsequently aggravates chronic rejection after transplantation. This may explain the clinical difference in long-term function between lungs from cadaveric donors and living donors.